1996
DOI: 10.1093/oxfordjournals.molbev.a025693
|View full text |Cite
|
Sign up to set email alerts
|

Deep-level diagnostic value of the rDNA-ITS region

Abstract: The similarity of certain reported angiosperm rDNA internal transcribed spacer (ITS) region sequences to those of green algae prompted our analysis of the deep-level phylogenetic signal in the highly conserved but short 5.8S and hypervariable ITS2 sequences. We found that 5.8S sequences yield phylogenetic trees similar to but less well supported than those generated by a ca. 10-fold longer alignment from rDNA-18S sequences, as well as independent evidence. We attribute this result to our finding that, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
92
0
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 41 publications
7
92
0
3
Order By: Relevance
“…In Halimeda, however, elevated rates of SSU regions in comparison to those of other green algae (Zechman et al, 1999) close in on depressed rates among ITS regions. The depression is expected because of a relatively high proportion of conserved functional core positions Hershkovitz and Lewis, 1996) in the short sequences of Halimeda (this study) in comparison to much longer ones found in other green algae (e.g., Bakker et al, 1995a,b).…”
Section: Sequence Comparisons and Phylogenetic Analysesmentioning
confidence: 56%
See 2 more Smart Citations
“…In Halimeda, however, elevated rates of SSU regions in comparison to those of other green algae (Zechman et al, 1999) close in on depressed rates among ITS regions. The depression is expected because of a relatively high proportion of conserved functional core positions Hershkovitz and Lewis, 1996) in the short sequences of Halimeda (this study) in comparison to much longer ones found in other green algae (e.g., Bakker et al, 1995a,b).…”
Section: Sequence Comparisons and Phylogenetic Analysesmentioning
confidence: 56%
“…Secondary structure models generated with RNAdraw (Matzura and Wennborg, 1996) allowed adjustment of the alignment in variable regions. Delineation of subunit and spacer regions was according to Hershkovitz and Lewis (1996). Matrices of pair-wise Kimura 2-parameter distances were calculated (PAUP*) for each sequence region separately and then normalized by dividing obtained values by their corresponding entries in the matrix of ITS-2 distances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences were aligned using Clustal W (Thompson et al 1994) in the Bioedit 4.5.8 computer package (Hall 1999). ITS regions recognition in the alignment was done according to Hershkovitz & Lewis (1996). The number of different haplotypes was calculated with the DAMBE computer program (Xia 2000), and the number of polymorphic sites was calculated using MEGA 2.1 (Kumar et al ).…”
Section: Methodsmentioning
confidence: 99%
“…RFLP and sequencing of the intergenic spacers (ITS, IGS1) of the rDNA gene complex of Pisolithus collected beneath A. quanzensis, P. caribaea and E. camaldulensis were undertaken because these regions are known to be variable at the inter-and intraspecific level (Gardes et al, 1991 ;Henrion, Le Tacon & Martin, 1992 ;Appel & Gordon, 1996 ;Kretzer et al, 1996). In addition, ITS region sequences can diagnose phylogenetic relationships at many phylogenetic levels (Hershkovitz & Lewis, 1996). Our sampling identified three distinct RFLP haplotypes, each specific to a single host.…”
mentioning
confidence: 99%